Safety issues and neurological improvement following C1-C2 fusion using C1 lateral mass and C2 pedicle screw in atlantoaxial instability - Kwan, M.K.; Chan, C.Y.W.; Kwan, T.C.C.; Gashi, Y.N.; Saw, L.B. (2010)
The evolution of instrumentation methods for C1-C2 fusion from the use of posterior wiring methods to transarticular screws and C1 lateral mass with C2 pedicle screw construct have improved fusion rates to almost 100. However, the C1 lateral mass and C2 pedicle screw technique is technically demanding. This is a prospective review of a series of ten patients who was planned for C1-C2 fusion using C1 lateral mass and C2 pedicle screw technique between January 2007 and June 2009. The procedure was converted to occipital cervical fusion due to a fracture of a hypoplastic lateral mass-posterior arch complex in one patient and Gallie fusion due to a vertebral artery injury in another. Eight patients underwent the C1-C2 fusion using C1 lateral mass and C2 pedicle screw successfully without any complications. The union rate was 100 with an average union time of 5.3 months (range from 3 to 8 months). Postoperatively, the patients achieved an average of one Frankel grade neurological improvement. In conclusion, this technique provides an excellent union rate and good neurological recovery.